Genetic and environmental factors shape the host response to Helicobacter hepaticus: insights into IBD pathogenesis - Jeffery, RL; Ilott, NE; Powrie, F (Elsevier, 2021)
Pathobionts are members of the gut microbiota with the capacity to cause disease when there is malfunctioning intestinal homeostasis. These organisms are thought to be major contributors to the pathogenesis of inflammatory bowel disease (IBD), a group of chronic inflammatory disorders driven by dysregulated responses towards the microbiota. Over two decades have passed since the discovery of Helicobacter hepaticus, a mouse pathobiont which causes colitis in the context of immune deficiency. During this time, we have developed a detailed understanding of the cellular players and cytokine networks which drive H. hepaticus immunopathology. However, we are just beginning to understand the microbial factors that enable H. hepaticus to interact with the host and influence colonic health and disease. Here we review key H. hepaticus-host interactions, their relevance to other exemplar pathobionts and how when maladapted they drive colitis. Further understanding of these pathways may offer new therapeutic approaches for IBD.